Análise do Programa Territórios da Cidadania do Agreste Meridional de Pernambuco : capital social e o processo de mobilização para repasses de recursos - BRANCO, Gilberto (2014)
This study aims to analyze the program Territories of Citizenship Program at Southern Wasteland in Pernambuco from the mobilization process for transfer of funds, and the role of existing social capital in these recipients’ municipalities with a view to sustainable development. The study is based on the concept of social capital through the formation of " durable networks of relationships " , in the viewpoint of Pierre Bourdieu (2007 ) as well as in models of public policy analysis : institutional , interest groups and the model elite, and the historical origin of patronage and corruption as "Rent -seeking" behavior. Methodologically were used the research data held by the Secretary of Territorial Development - STD / MDA , through the creation of the Research Index of Social Capital Territory Wasteland South , which was then ranked by municipalities . From this result, the interviews with the actors involved were ordered. These were performed from November two thousand and thirteen through February two thousand and fourteen. Based on the survey results the following hypothesis was examined: - There is a growing relationship between social capital and the transfer of resources from the Territories of Citizenship Program. Additionally, it moved to answer the following research question of the thesis: - What are the mechanisms for transferring resources to meet the goals of the TCP and the role of social capital in this process? Among the key findings it can be highlighted: according to the model of institutional policy analysis, social capital in the territory is not yet capable of enhancing access to resources of the program because according to the same model, although it is consistently present in base (present in the municipalities association) there is a "gap" between the base and the higher courts, which depends on the transfer of funds from TCP needed to municipalities. Being responsible for finalizing the process by which resources are transformed into benefits for the target population of TCP. The cause of the "gap" has been found in the fact that the greater presence of social capital implies more efficient supervision, required greater legality of the transfer of funds process. Given the historic political vices in the country and continuing this trend, it was found that there is evidence of corruption and cronyism in the transfer process and explained that they have allowed greater access of some municipalities in relation to other participants in the Program.